Writing Ability with Metaphorming Approach: A Systematic Review - Suwartini, Yati; Lustyantie, Ninuk; Suseno, Muchlas; Supriyati, Yetti (International Journal of Education, 2021)
Metaphorming is a new way of brainstorming that covers all aspects and complexity of students’ creative thinking skills. This approach enhances fast-thinking ability and creativity, allowing them to connect something that is known with a new one for better problem-solving. The purpose of this study was to conduct a systematic review on how to improve students’ writing skills through a metaphorming approach. The methodology used was the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA). Furthermore, the writing skills were examined using a metaphorming approach from 5 databases with several articles, including 143, 58, 4, 198, and 23 from Microsoft Academic, Scopus, JSTOR, crossref, and EBSCO, respectively. This study’s results analyzed 11 focus studies related to metaphorming effects. The study strategy was developed by formulating the problem, combining descriptors and keywords, and the year of publication. To choose the correct studies for review, three independent reviewers carried out abstract and full-text selection and research analysis. In this regard, 426 articles were obtained, though only 43 were selected for review. The results showed that mapping the metaphorming approach could improve writing skills. Therefore, this study provides valuable information about the metaphorming approach for better writing skills and can also be used to examine learning and teaching materials development.